The Dilemma of Coexisting Nevoid Hyperkeratosis of the Nipple and Areola in Mycosis Fungoides: A Report of Three Cases - Algun Polat Ekinci; Sule Ozturk Sari; Nesimi Buyukbabani; Can Baykal (MDPI AG, 2015)
Nevoid hyperkeratosis of the nipple and areola (NHNA) is a rare clinicopathological entity showing persistent and strictly localized hyperkeratotic lesions of the nipple, areola or both with unknown etiopathogenesis. A similar clinical appearance may also be seen in different diseases with specific histopathological features. There are a few anecdotal reports on the association of NHNA with mycosis fungoides (MF), but they do not describe a uniform condition. In this report, we present 3 patients with hyperkeratotic lesions of the nipple and areola associated with MF but showing different histopathological features. We also review similar cases in the literature and discuss possibilities concerning this association. Two of our cases represent the association between MF and NHNA without histopathological features of MF on the nipple-areola complex. The other case represents hyperkeratosis of the nipple and areola with specific histological and immunohistochemical features of MF. Hence, we would like to hypothesize that MF may involve the nipple and areola and have an appearance similar to NHNA. Intriguingly, however, NHNA may occasionally also be seen in association with MF. However, this peculiar association requires further explanation.